2021
DOI: 10.1007/s12185-021-03197-5
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between insufficient plasma exchange and fatal outcomes in Japanese patients with immune-mediated thrombotic thrombocytopenic purpura

Abstract: Plasma exchange (PEX) using fresh frozen plasma has considerably reduced the mortality rate in patients with immunemediated thrombotic thrombocytopenic purpura (iTTP). However, some patients still do not survive even with treatment, but little information is available regarding which treatment these patients received. This study was conducted to obtain this information in 240 patients who met the current iTTP diagnostic criteria and completed at least 30 days of follow-up except for deceased cases. These patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As for treatments for immune-mediated TTP, prompt and adequate plasma exchange [119][120][121] and corticosteroid therapy have been used [122]. Plasma exchange can remove unusually large VWF multimers, remove anti-ADAMTS13 antibodies, and replenish fresh ADAMTS13 [123].…”
Section: Ttpmentioning
confidence: 99%
“…As for treatments for immune-mediated TTP, prompt and adequate plasma exchange [119][120][121] and corticosteroid therapy have been used [122]. Plasma exchange can remove unusually large VWF multimers, remove anti-ADAMTS13 antibodies, and replenish fresh ADAMTS13 [123].…”
Section: Ttpmentioning
confidence: 99%
“…A Japanese retrospective study revealed that 26 out of 32 patients experienced sudden death, mostly following radical hypotension and bradycardia. The median follow-up time after admission was 5.0 days, and nine patients underwent autopsy and had cardiac microvascular thrombi in arterioles [57]. The UK group reported a retrospective study on cardiac involvement in acute iTTP.…”
Section: Troponin-t/i and Glasgow Coma Score And Their Link With Acut...mentioning
confidence: 99%
“…The risk of relapse is estimated to be about 40-55% over the 7-8 years following an acute event [2,3], or about 2% per month [4]. In a US registry study, the 20-year mortality rate was approximately 20% among individuals with iTTP [2], and in Japan, the 12-month rate of iTTP-related mortality has been reported as approximately 13% [5].…”
Section: Introductionmentioning
confidence: 99%